Malignant transformation of monostotic fibrous dysplasia into angiosarcoma in the proximal tibia - Selin Narter; Ulviye Yalcinkaya; Muhammet S Bilgen; Zeynep Yazici (Wolters Kluwer Medknow Publications, 2021)
The majority of bone angiosarcomas are primary tumors while secondary angiosarcomas arise after radiation therapy or bone infarctus. This article presents a case of malignant transformation of monostotic fibrous dysplasia into angiosarcoma. An 80-year-old female presented with pain on right cruris. Radiological examination revealed a lesion with lytic areas and destruction of cortical bone on right tibia. Gross and histopathological examination showed two areas with an abrupt transition. The solid component was composed of curved, immature bony trabeculae in a fibroblastic stroma. The other component involved epitheloid cells forming slit-like vascular spaces. The diagnosis of angiosarcoma and fibrous dysplasia was given. Malignant transformation of fibrous dysplasia into angiosarcoma is extremely rare; as this is the sixth case in the existing literature. Prognosis of fibrous dysplasia is generally good and less than 1% of the patients develop a malignant tumor. Therefore, patients with fibrous dysplasia should be offered a life-long follow-up.